1963
DOI: 10.1139/p63-116
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Broadening of Impurity Spectral Lines: I. General Theory

Abstract: The theory of the phonon broadening of impurity spectral lines is discussed within the framework of a Kubo-type formulation of the adiabatic dielectric susceptibility and the subsequent calculation of this using double-time Green's functions. The interaction of the bound electron (or hole) with the lattice vibrations is assumed to be weak and is treated as a small perturbation of the independent systems of electron and vibrating lattice; the use of the adiabatic approximation is thereby avoided. The cases in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…D(H,O) donor in ultra-pure germanium. They found that the excited state lifetime approaches the fundamental limit given by final state mixing [20,21].…”
Section: Hall Effect and Photothermal Ionization Spectroscopymentioning
confidence: 99%
“…D(H,O) donor in ultra-pure germanium. They found that the excited state lifetime approaches the fundamental limit given by final state mixing [20,21].…”
Section: Hall Effect and Photothermal Ionization Spectroscopymentioning
confidence: 99%
“…, f 1 (1) , , , , , , , , , , , , , , , , , A, (1) f, (1) , , The p-states of S+ and SO resemble each other very much with one major difference.…”
Section: The Sulfur Donor In Siliconmentioning
confidence: 99%
“…This result suggested that a fundamental lifetime broadening limit had been found and that all inhomogeneous broadening effects were eliminated. Barrie and Nishikawa [1,2] proposed that this lifetime broadening was a result of phonon-assisted transitions from the excited state to other near-lying…”
Section: Isotopically Enriched Siliconmentioning
confidence: 99%
“…Barrie and Nishikawa. [16,17] proposed more than twenty years ago that final state interactions are the main cause for line broadening. Kane [18] had shown earlier that phonon emission or absorption-assisted transitions contribute to a very broad background.…”
Section: Photothermal Ionization Spectroscopy (Ptis) With Ultra-pure mentioning
confidence: 99%